ANALISIS HEDONIC SHOPPING MOTIVATION MASYARAKAT MENGGUNAKAN DOMPET DIIGITAL SHOPEE PAYLATER DALAM PERSPEKTIF SYARIAH - Niken Rika Saputri; Sandra Dewi (Jurnal Ekonomi dan Bisnis, 2024)
This thesis was written by Niken Rika Saputri, Nim 3320034 Student of the Sharia Banking Bachelor's Study Program, Faculty of Economics and Islamic Business, Bukittinggi State Islamic University. With the title "Analysis of Hedonic Shopping Motivation of People Using the Shopee PayLater Digital Wallet in a Sharia Perspective". The background of this research is to determine the hedonic shopping motivation of Shopee Paylater from a sharia perspective in the Sidodadi Limau Putu District community. West Pasaman, hedonic shopping motivation is the urge to shop based on desire, pleasure and pleasant experiences. This research aims to identify the hedonic shopping motivation of people who use Shopee Paylater from a sharia perspective.This research uses descriptive qualitative research methods and the research approach used is field research. The data collection techniques used were observation, questionnaires and interviews. Meanwhile, the data analysis techniques used are data reduction, data presentation, and drawing conclusions. The research results show that Shopee PayLater on the Shopee marketplace has a very bad impact on finances. Apart from having a bad impact on finances, Shopee PayLater also makes it easy for them to get used to debt and make purchases which can make them get used to debt and make purchases which can make them engage in consumptive habits. so it can cause them to buy impulsively because of Shopee PayLater with 'Buy now, Pay later'. Allah SWT forbids usury, where usury is an addition or increase that is prohibited in financial transactions according to Islamic sharia. Shopee PayLater gives interest to those who borrow, therefore using Shopee PayLater is Haram, because there are additional fees or excess of the amount lent in percent and monthly.